Method for preparing benzene, toluene and p-xylene by using raw material containing furan structure

By constructing an ordered mesoporous tin oxide-anchored platinum-tin intermetallic compound catalyst, the problem of low yield of biomass-based BTX aromatic hydrocarbons is solved, and the efficient catalytic conversion of biomass-based furan compounds is achieved, with high yield and catalysts having Good recyclability and activity/selectivity.

CN119462316APending Publication Date: 2025-02-18SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411604177.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the use of renewable lignocellulose to prepare biomass-based BTX, the aromatic yield is low and the catalyst construction efficiency is low, which affects its large-scale industrial application.

Method used

By rationally building a multifunctional ordered mesoporous tin oxide-anchored platinum-tin intermetallic compound catalyst, the crystal phase of platinum-based nanoparticles, the thickness of tin oxide covering layer, and the density of acidic sites in ordered mesoporous tin oxide, we can achieve Highly efficient catalytic conversion of biomass-based furan compounds to BTpX.

Benefits of technology

The efficient catalytic conversion of furan, furfural and 5-hydroxymethylfurfural to benzene, toluene and paraxylene was achieved, with yields as high as 94.6%, 94.2% and 95.2%, respectively. The catalyst preparation method is simple, the material is uniform, and the purity is high. , complete structure, good recyclability and activity/selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462316A_ABST
    Figure CN119462316A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing benzene, toluene and p-xylene by using a raw material containing a furan structure. According to the method, an ordered mesoporous tin oxide anchored platinum-tin intermetallic compound is adopted as a catalyst, in the presence of hydrogen and a solvent, furan, furfural and 5-hydroxymethylfurfural are catalytically converted into benzene, methylbenzene and p-xylene through hydrogenolysis and / or Diels-Alder reaction respectively, the reaction temperature is 30-200 DEG C, the reaction time is 0.5-30 h, and the hydrogen pressure is 0.01-4 Mpa; the catalytic system provided by the invention can catalytically convert furan, furfural and 5-hydroxymethylfurfural into corresponding benzene, toluene and p-xylene in a green and sustainable manner under relatively mild conditions, and shows excellent yield and stability. The technical process is green and environment-friendly, the product yield is high, the preparation method of the catalyst is simple, and the obtained material is very uniform, high in purity, complete in structure, controllable in ordered mesoporous structure and high in mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical synthesis and nano material synthesis, and specifically relates to a technology for preparing benzene, toluene and p-xylene respectively from furan, furfural and 5-hydroxymethylfurfural and a method for preparing a catalyst thereof. Background Art

[0002] Aromatic hydrocarbons, especially benzene, toluene and xylene (collectively referred to as BTX), play an indispensable role in our daily lives due to their wide range of applications from healthcare to polymer industry, with an annual global consumption of more than 140 million tons and production growing by 2-6% per year (PP Van Uytvanck, G. Haire, PJ Marshall, JS Dennis, ACS Sutain. Chem. Eng. 2017, 5, 4119-4126; DSSholl, RP Lively, Nature 2016, 532, 435-437; AM Niziolek, O. Onel, C. A. Floudas, AI ChE J 2016, 62, 1531-1556; AM Niziolek, O. Onel, YA Guzman, C. A. Floudas, Energy Fuels 2016, 30, 4970-4998). However, to date, the production of BTX still heavily relies on limited, non-renewable fossil fuels, either obtained through catalytic reforming of naphtha or through steam cracking of hydrocarbons, which has brought terrible energy crises and serious environmental pollution problems to the world (K. Cheng, W. Zhou, J. Kang, S. He, S. Shi, Q. Zhang, Y. Pan, W. Wen, Y. Wang, Chem 2017, 3, 334-347; I. Scodeller, S. Mansouri, D. Morvan, E. Muller, K. de Oliveira Vigier, R. Wischert, F. Angew.Chem.Int.Ed.2018 2018,57,10510-10514). Therefore, renewable lignocellulose, including cellulose, hemicellulose and lignin, is the most promising candidate for replacing existing petroleum feedstocks to produce biomass-based BTX (A.Nekhaev, A.Maksimov, Pet.Chem 2021,61,15-34; D MAlonso, SG Wettstein, JA Dumesic, Chem.Soc.Rev.2012,41,8075-8098). However, the aromatic content in the direct catalytic pyrolysis product of lignocellulose is only ~23%, and the BTX yield is even lower, only ~12%, which seriously hinders its large-scale industrial application (Y.-T.Cheng, J.Jae, J.Shi, W.Fan, GW Huber, Angew.Chem.Int.Ed.2011,51,1416-1419). It is noteworthy that the hydrolysis and subsequent dehydration of hemicellulose / cellulose can maturely produce the basic molecules of furan, furfural (FFA) and 5-hydroxymethylfurfural (HMF) (Y. Román-Leshkov, JN Cheheda, J A Dumesic, Science 2006, 312, 1933-1937; C. Xu, E. Paone, D. Rodríguez-Padrón, R. Luque, F. Mauriello, Chem. Soc. Rev. 2020, 49, 4273-4306), which are the basic biomass-derived raw materials for future biorefining schemes and are expected to be further converted into benzene, toluene and para-xylene (collectively referred to as BTpX) through hydrogenolysis and / or Diels-Alder reactions, respectively. Unfortunately, there has been no report on the research on the series upgrading of FFA to produce toluene, and there are few studies on the series upgrading of HMF and furan to produce p-xylene and benzene, but the yields are still unsatisfactory, less than 85% and 35%, respectively, and are carried out under unsatisfactory reaction conditions (250-300°C, 4.0-6.2MPa) (L.Tao, T.-H.Yan, W.Li, Y.Zhao, Q.Zhang, Y.-M.Liu, M.M.Wright, Z.-H.Li, H.-Y.He, Y.Cao, Chem 2018, 4, 2212-2227; Y.Zhao, K.-Z.Wang, Z.-H.Sun, Q.Zhang, Z.-J.Wang, Y.-M.Liu, H.-Y.He, Y.Cao, Green Chem 2022, 24, 4095-4107).In addition, all these studies used ethylene as the diol to react with biomass-based furans for Diels-Alder reactions, and ethylene also mainly comes from petroleum feedstocks, thus seriously affecting their sustainability (J. Yin, C. Shen, X. Feng, K. Ji, L. Du, ACS Sustain. Chem. Eng. 2018, 6, 1891-1899). It is highly desirable to use sustainable bio-based raw material acrylic acid (AA) instead of ethylene to synthesize BTpX from the above biomass-based furans in high yield, but it has not yet been reported. Taking the cascade upgrading of HMF to prepare pX as an example, the main obstacle is the difficulty in simultaneously achieving the efficient hydrogenolysis of HMF to produce 2,5-dimethylfuran (DMF) and the subsequent Diels-Alder reaction between DMF and AA. These two reactions require completely different types of catalytic sites (L. Tao, T.-H. Yan, W. Li, Y. Zhao, Q. Zhang, Y.-M. Liu, M. M. Wright, Z.-H. Li, H.-Y. He, Y. Cao, Chem 2018, 4, 2212-2227; G.-H. Wang, J. Hilgert, F. H. Richter, F. Wang, H.-J. Bongard, B. Spliethoff, C. Weidenthaler, F. Schüth, Nat. Mater. 2014, 13, 293-300). Therefore, the rational construction of catalysts to tightly integrate the desired active sites into a single structure with good compatibility is expected to realize the above-mentioned sequential reactions of biomass-based furan to BTpX, but it remains a daunting task.

[0003] In recent decades, platinum-based catalysts have been widely used in complex hydrogenolysis reactions of furan compounds containing formyl and / or hydroxyl groups due to their excellent hydrogen dissociation ability and hydrogenolysis ability of C=O and CO groups (G.-H. Wang, J. Hilgert, FHRichter, F. Wang, H.-J. Bongard, B. Spliethoff, C. Weidenthaler, F. Schüth, Nat. Mater. 2014, 13, 293-300; X. Lan, T. Wang, ACS Catal. 2020, 10, 2764-2790.). Among them, platinum-based intermetallic nanoparticles (iNPs) with periodic atomic stoichiometric arrangements are considered to be effective catalysts for various selective hydrogenolysis reactions due to their strong d-orbital interactions and electronic effects, which can not only delay the metal leaching of the alloy to enhance its stability, but also further improve the catalytic activity and selectivity through synergistic catalysis (X. Lan, Y. Wang, B. Liu, Z. Kang, T. Wang, Chem. Sci 2024, 15, 1758-1768; C.-L. Yang, L.-N. Wang, P. Yin, J. Liu, M.-X. Chen, Q.-Q. Yan, Z.-S. Wang, S.-L. Xu, S.-Q. Chu, C. Cui, Science 2021, 374, 459-464). On the other hand, numerous studies have shown that the Diels-Alder reaction of furans with diols can be catalyzed by acidic sites (I. F. Teixeira, B. T. Lo, P. Kostetskyy, M. Stamatakis, L. Ye, C. C. Tang, G. M. Pourmpakis, S. C. E. Tsang, Angew. Chem. Int. Ed. 2016, 55, 13061-13066), among which some acidic metal oxides have become excellent candidates for this challenging transformation due to their low cost, tunable acidity and good stability (J. Yin, C. Shen, X. Feng, K. Ji, L. Du, ACS Sustain. Chem. Eng. 2018, 6, 1891-1899). In addition, an increasing number of studies have shown that the introduction of ordered mesopores into various metal oxides can significantly improve the accessibility of their acidic sites, thereby greatly enhancing their catalytic activity (S. Xiao, L. Wang, Z. Qin, X. Chen, L. Chen, Y. Li, K. Shen, ACSCentral Sci. 2024, 10, 374-384).Therefore, coupling platinum-based iNPs with ordered mesoporous metal oxides with good acidity can provide a promising route for constructing bifunctional catalysts to achieve tandem upgrading of biomass-based furans to BTpX products. However, conventional strategies for integrating iNPs with metal oxides into a single catalyst, such as impregnation (W. Yu, MD Porosoff, JG Chem. Rev 2012, 112, 5780-5817), chemical vapor deposition (MT Schaal, AC Pickerell, CT Williams, JR Monnier, J. Catal. 2008, 254, 131-143), and atomic layer deposition (H. Wang, C. Wang, H. Yan, H. Yi, J. Lu, J. Catal. 2015, 324, 59-68), are inefficient in optimizing catalytic active sites by exploiting their electronic, geometric, and compositional effects. Therefore, efficient and controllable preparation of highly active iNPs-coupled ordered mesoporous metal oxide catalysts is urgently needed for the tandem upgrading of biomass-based furan compounds to BTpX. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the existing method for preparing BTpX, and to catalytically convert biomass-based furan compounds into high-yield BTpX products by rationally constructing a multifunctional ordered mesoporous tin oxide anchored platinum tin intermetallic compound catalyst. Among them, the crystal phase of the platinum-based nanoparticles, the thickness of the tin oxide coating layer, and the density of acid sites in the ordered mesoporous tin oxide can be precisely adjusted by simply regulating the reduction temperature. Impressively, the catalytic system can achieve the catalytic conversion of furan, furfural and 5-hydroxymethylfurfural to benzene, toluene and p-xylene, with yields of up to 94.6%, 94.2% and 95.2%, respectively. It is a new type of tandem catalytic system that can achieve the preparation of BTpX products from the corresponding biomass-based furan compounds. The technology of the present invention is green and environmentally friendly, with a high product yield, and the preparation method of its catalyst is simple, the obtained material is very uniform, high purity, complete structure, controllable ordered mesoporous structure, and strong mechanical strength.

[0005] The present invention is achieved through the following technical solutions.

[0006] The present invention provides a simple and novel strategy to synthesize ordered mesoporous tin oxide anchored platinum tin intermetallic compound catalysts to achieve the catalytic conversion of biomass-based furan compounds into the corresponding BTpX products. The crystalline phase of the platinum-based nanoparticles, the thickness of the tin oxide capping layer, and the density of acidic sites in the ordered mesoporous tin oxide can be precisely adjusted by simply regulating the reduction temperature.

[0007] Therefore, the present invention provides a method for preparing benzene, toluene and p-xylene using raw materials containing furan structures. When preparing benzene, toluene and p-xylene, the raw materials containing furan structures are furan, furfural and 5-hydroxymethylfurfural respectively. An ordered mesoporous tin oxide-anchored platinum-tin intermetallic compound is used as a catalyst. In the presence of hydrogen and a solvent, furan, furfural and 5-hydroxymethylfurfural are catalytically converted into benzene, toluene and p-xylene respectively through hydrogenolysis and / or Diels-Alder reaction. The raw materials containing furan structures are also called biomass-based furan compounds, and the mass ratio of the raw materials containing furan structures to the catalyst is 1:0.1-1.

[0008] In a specific embodiment, the solvent is one of tetrahydrofuran, N,N-dimethylformamide and methanol.

[0009] In a specific embodiment, the hydrogen pressure is 0.01-4 MPa.

[0010] In a specific embodiment, the reaction time is 5 to 30 hours.

[0011] In a specific embodiment, the reaction temperature is 30-200°C.

[0012] In a specific embodiment, the preparation method of the catalyst ordered mesoporous tin oxide anchored platinum tin intermetallic compound comprises the following steps:

[0013] 1) Ordered mesoporous tin oxide materials were synthesized using ordered silica as a template;

[0014] 2) Adsorbing the ordered mesoporous tin oxide material obtained in step 1) with a platinum metal precursor solution by an equal volume impregnation method, and drying;

[0015] 3) The powder product obtained in step 2) is reduced at high temperature to obtain an ordered mesoporous tin oxide anchored platinum-tin intermetallic compound material.

[0016] In a specific embodiment, the platinum metal precursor solution in step 2) is one of chloroplatinic acid, platinum chloride and platinum nitrate solutions.

[0017] In a specific embodiment, the drying in step 2) is vacuum drying, the drying temperature is 50 to 80° C., and the drying time is 6 to 24 hours.

[0018] In a specific embodiment, the calcination atmosphere in step 3) is H2 / Ar, the heating rate is 1-5°C / min, the temperature is 200-500°C, and the time is 1-6 hours.

[0019] The present invention also provides a catalyst prepared by the method as described above, wherein the catalyst is an ordered mesoporous tin oxide anchored platinum-tin intermetallic compound, wherein the ordered mesoporous tin oxide has a length of 800 to 1200 nm, a width of 550 to 750 nm, and a pore size of 20 to 27 nm, and the crystal phase of the platinum-tin intermetallic nanoparticles is adjustable, and can be converted from Pt nanoparticles (NPs) to Pt3Sn1 intermetallic nanoparticles (iNPs) and finally to Pt1Sn1 iNPs as the temperature increases.

[0020] The ordered mesoporous tin oxide anchored platinum tin intermetallic compound material prepared by the present invention has potential application prospects in realizing the green and sustainable catalytic conversion of various biomass-based furan compounds into corresponding BTpX products.

[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0022] This paper proposes for the first time a simple and novel strategy to synthesize ordered mesoporous anchored platinum-tin intermetallic compound catalysts to achieve the catalytic conversion of various biomass-based furan compounds into corresponding BTpX products. The results show that as the reduction temperature increases from 200°C to 350°C, Pt NPs are first formed on the surface of OM-SnO2, then converted into Pt3Sn1 iNPs, and finally converted into Pt1Sn1 iNPs, and the SnO2 capping layer thereon gradually thickens. Therefore, this work provides a new toolbox for enriching the family of highly stable intermetallic nanoparticles on reducible supports, and can be used for other cascade catalytic reactions. This method is simple to operate, the preparation process is green and environmentally friendly, the prepared products are of high purity, controllable structure, strong mechanical strength, and can be used directly as catalysts. Moreover, the preferred catalyst can effectively achieve the catalytic conversion of biomass-based furan compounds into corresponding BTpX products with a yield of ≥94%, and also has good recyclability and excellent activity / selectivity, indicating that it has great potential in the green and sustainable catalytic conversion of biomass-based furan compounds into corresponding BTpX products. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The scanning electron microscope image and particle size distribution diagram of the ordered silica template prepared in Example 1 of the present invention.

[0024] Figure 2 The scanning electron microscope image and size distribution diagram of the ordered mesoporous tin oxide prepared in Example 2 of the present invention.

[0025] Figure 3 Scanning electron microscope images and pore size distribution diagrams of ordered mesoporous tin oxide anchored Pt-based nanoparticle materials (named Pt@OM-SnO2-T) prepared in Examples 3-6 of the present invention at different reduction temperatures.

[0026] Figure 4 This is a high-magnification transmission electron micrograph of Pt@OM-SnO2-T prepared in Examples 3-6 of the present invention and a size distribution diagram of the corresponding Pt-based nanoparticles thereon.

[0027] Figure 5 High-angle annular dark-field scanning transmission electron microscopy images and corresponding energy-dispersive X-ray elemental maps of the corresponding Pt-based nanoparticles on Pt@OM-SnO2-T prepared in Examples 3-6 of the present invention.

[0028] Figure 6 Atomic-resolution scanning transmission electron microscopy images of the corresponding Pt-based nanoparticles on Pt@OM-SnO2-T prepared in Examples 3-6 of the present invention and the line intensity distribution diagram corresponding to the direction marked by the lines in a1-d1.

[0029] Figure 7 This is the X-ray diffraction pattern of Pt@OM-SnO2-T prepared in Examples 3 to 6 of the present invention.

[0030] Figure 8 This is a scanning electron microscope image of the ordered mesoporous tin oxide anchored Pt-based nanoparticle material (named Pt@OM-SnO2-500) prepared in Example 7 of the present invention and reduced at 500°C.

[0031] Fig. 9 The catalytic stability performance evaluation results of the Pt@OM-SnO2-350 material prepared in Example 5 of the present invention for catalytic conversion of biomass-based furan compounds into biomass-based BTpX. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is further described in detail below in conjunction with the drawings and embodiments, but the implementation of the present invention is not limited thereto.

[0033] Example 1

[0034] The preparation of the ordered silica template comprises the following steps:

[0035] 0.24g of lysine and 210g of ethanol were mixed in a 500mL flat-bottom flask and magnetically stirred for 10min. Then 16.1g of tetraethyl silicate was added to the above flask, and the resulting mixture was vigorously stirred at 90°C for 48h. Subsequently, the above silica sol was hydrothermally aged at 100°C for 24h as a seed to grow a larger silica template. Next, 16.1g of tetraethyl silicate was added to the above silica colloidal solution and vigorously stirred at 90°C for 24h. Subsequently, the water in the silica colloidal solution was slowly evaporated in a 70°C oven for 24h to form an ordered silica template with an average particle size of 22nm. Finally, the obtained 22nm ordered silica template was calcined to remove the lysine adsorbed on the silica nanospheres. The temperature program was 5°C per minute to reach 600°C, maintained for 12h, and the atmosphere was air.

[0036] Figure 1 The scanning electron microscope image of the ordered silica template prepared in Example 1 and the size distribution diagram of the particles clearly show that highly ordered silica nanoparticles with a size of about 22 nm were successfully synthesized.

[0037] Example 2

[0038] The preparation of ordered mesoporous tin oxide (OM-SnO2) with a pore size of 22 nm comprises the following steps:

[0039] 10 mL of deionized water and 10 mL of ethanol were added to the inner lining of a 100 mL autoclave, and then 1.35 g of SnCl4·5H2O was added to the above solution. After the above mixture was ultrasonically treated for 10 min, 1.8 mL of 37% HCl was added, and the mixture was further ultrasonically treated for 10 min to disperse it, and then 1 g of the ordered silica template prepared in Example 1 was added, and the sealed container was heated at 180°C for 12 h at a heating rate of 2°C / min. Subsequently, the ordered silica template was etched with a 2 mol / L NaOH solution for 12 h, washed with deionized water and ethanol in turn, and centrifuged to obtain OM-SnO2, whose pore size was 22 nm.

[0040] Figure 2 The scanning electron microscope image of OM-SnO2 prepared in this example shows that it has a good olive shape and uniform size, with a width of about 620nm and a length of about 1000nm.

[0041] Example 3

[0042] The preparation of ordered mesoporous tin oxide supported Pt-based nanoparticles (Pt@OM-SnO2-200) under reduction at 200°C comprises the following steps:

[0043] First, 100 mg OM-SnO2 was impregnated by adding 100 μl of an aqueous solution containing 5.4 mg H2PtCl6·6H2O (Pt loading was 2 wt%). After ultrasonic treatment for 1 h, the slurry was dried overnight under vacuum at 50 °C. Finally, the obtained powder sample was placed in a tube furnace and pyrolyzed from room temperature to 200 °C at a rate of 2 °C / min, and then maintained at the target reduction temperature for 2 h in a hydrogen atmosphere to obtain the corresponding Pt@OM-SnO2-200.

[0044] Example 4

[0045] The preparation of ordered mesoporous tin oxide supported Pt-based nanoparticles (Pt@OM-SnO2-300) under reduction at 300°C comprises the following steps:

[0046] First, 100 mg OM-SnO2 was impregnated by adding 100 μl of an aqueous solution containing 5.4 mg H2PtCl6·6H2O (Pt loading was 2 wt%). After ultrasonic treatment for 1 h, the slurry was dried overnight under vacuum at 50 °C. Finally, the obtained powder sample was placed in a tube furnace and pyrolyzed from room temperature to 300 °C at a rate of 2 °C / min, and then maintained at the target reduction temperature for 4 h in a hydrogen atmosphere to obtain the corresponding Pt@OM-SnO2-300.

[0047] Example 5

[0048] The preparation of ordered mesoporous tin oxide supported Pt-based nanoparticles (Pt@OM-SnO2-350) under reduction at 350°C comprises the following steps:

[0049] First, 100 mg OM-SnO2 was impregnated by adding 100 μl of an aqueous solution containing 5.4 mg H2PtCl6·6H2O (Pt loading was 2 wt%). After ultrasonic treatment for 1 h, the slurry was dried overnight under vacuum at 50 °C. Finally, the obtained powder sample was placed in a tube furnace and pyrolyzed from room temperature to 350 °C at a rate of 2 °C / min, and then maintained at the target reduction temperature for 4 h in a hydrogen atmosphere to obtain the corresponding Pt@OM-SnO2-350.

[0050] Example 6

[0051] The preparation of ordered mesoporous tin oxide supported Pt-based nanoparticles (Pt@OM-SnO2-400) under reduction at 400°C comprises the following steps:

[0052] First, 100 mg OM-SnO2 was impregnated by adding 100 μl of an aqueous solution containing 5.4 mg H2PtCl6·6H2O (Pt loading was 2 wt%). After ultrasonic treatment for 1 h, the slurry was dried overnight under vacuum at 50 °C. Finally, the obtained powder sample was placed in a tube furnace and pyrolyzed from room temperature to 400 °C at a rate of 2 °C / min, and then maintained at the target reduction temperature for 4 h in a hydrogen atmosphere to obtain the corresponding Pt@OM-SnO2-400.

[0053] Figure 3 The scanning electron microscope images and corresponding pore size distribution diagrams of Pt@OM-SnO2-T prepared in Examples 3 to 6 of the present invention show that all Pt@OM-SnO2-200, Pt@OM-SnO2-300 and Pt@OM-SnO2-350 still present a uniform olive-shaped morphology with well-maintained ordered mesopores (about 22 nm). However, when the reduction temperature is further increased to 400°C, the periodic mesopores of the generated Pt@OM-SnO2-400 begin to collapse because tin oxide will be reduced by H2 at high temperatures.

[0054] Figure 4 From the high-magnification transmission electron micrographs of Pt@OM-SnO2-T prepared in Examples 3 to 6 of the present invention and the size distribution diagrams of the platinum-based nanoparticles anchored thereon, it can be found that the platinum-based nanoparticles on Pt@OM-SnO2-200, Pt@OM-SnO2-300, Pt@OM-SnO2-350 and Pt@OM-SnO2-400 are highly dispersed, with average sizes of ~3.0, ~4.1, ~4.6 and ~5.3 nm, respectively. Figure 5 The high-angle annular dark field scanning transmission images and corresponding energy dispersive X-ray elemental maps of the corresponding Pt-based nanoparticles on Pt@OM-SnO2-T prepared in Examples 3 to 6 of the present invention indicate that platinum and tin elements are evenly distributed in the platinum-based nanoparticles of Pt@OM-SnO2-300, Pt@OM-SnO2-350 and Pt@OM-SnO2-400, but only platinum elements are observed in the nanoparticles of Pt@OM-SnO2-200. These results indicate that when reduced at 200°C, Pt nanoparticles are first formed on OM-SnO2, and when the reduction temperature is further increased, the Pt nanoparticles can be converted into PtSn alloy nanoparticles. Figure 6As shown in Figure 3, unlike the Pt nanoparticles in Pt@OM-SnO2-200, the Pt3Sn1 iNPs in Pt@OM-SnO2-300 have a Z contrast difference between platinum and tin, corresponding to an L12-type ordered structure, which is also confirmed by the corresponding intensity curves. Meanwhile, the Pt1Sn1 iNPs in both Pt@OM-SnO2-350 and Pt@OM-SnO2-400 show a layer-by-layer atomic arrangement, which can be attributed to their L10-type ordered structures. The above results clearly demonstrate that as the reduction temperature increases from 200°C to 350°C, Pt NPs are first formed on OM-SnO2, then transformed into Pt3Sn1 iNPs, and finally transformed into Pt1Sn1 iNPs, and the SnO2 capping layer thereon gradually thickens. Figure 7 X-ray diffraction patterns of Pt@OM-SnO2-T prepared in Examples 3 to 6 of the present invention. As shown in the figure, all samples show similar strong diffraction peaks, which can be attributed to the rutile phase of tetragonal SnO2 (JCPDS: 00-021-1250), indicating that the crystal structure of OM-SnO2 will not change at a suitable reduction temperature. As expected, new diffraction peaks of various platinum-based nanoparticles can be observed in the PXRD patterns of Pt@OM-SnO2-T. Specifically, Pt@OM-SnO2-200 shows two small diffraction peaks at 39.8° and 46.2°, which are related to the fcc structure of Pt NPs; Pt@OM-SnO2-300 shows two small diffraction peaks at 39.6° and 45.5°, which are related to the atomic structure of platinum nanoparticles. Pt@OM-SnO2-350 and Pt@OM-SnO2-400 show two small diffraction peaks at 41.5° and 44.1°, which correspond to the atomic ordered metal structure (Pm-3m space group) of Pt3Sn1 iNPs, while Pt@OM-SnO2-350 and Pt@OM-SnO2-400 show two small diffraction peaks at 41.5° and 44.1°, which correspond to the atomic ordered metal structure (P63 / mmc space group) of Pt1Sn1iNPs. In addition, Pt@OM-SnO2-400 shows two new peaks at 30.6° and 32.0°, which can be attributed to the (200) and (101) crystal planes of metallic tin (PDF#86-2264), respectively.

[0055] Example 7

[0056] The preparation of ordered mesoporous tin oxide supported Pt-based nanoparticles (Pt@OM-SnO2-500) under reduction at 500°C comprises the following steps:

[0057] First, 100 mg OM-SnO2 was impregnated by adding 100 μl of an aqueous solution containing 5.4 mg H2PtCl6·6H2O (Pt loading was 2 wt%). After ultrasonic treatment for 1 h, the slurry was dried overnight under vacuum at 50 °C. Finally, the obtained powder sample was placed in a tube furnace and pyrolyzed from room temperature to 500 °C at a rate of 2 °C / min, and then maintained at the target reduction temperature for 4 h in a hydrogen atmosphere to obtain the corresponding Pt@OM-SnO2-500.

[0058] Figure 8 The scanning electron microscope image of Pt@OM-SnO2-500 prepared in Example 7 of the present invention shows that further high-temperature reduction will cause the periodic mesoporous structure of Pt@OM-SnO2-500 to be almost completely destroyed. Therefore, we choose ≤400°C as the reduction temperature to prepare ordered mesoporous tin oxide-anchored platinum-tin intermetallic compound materials.

[0059] Example 8

[0060] This example provides a method for preparing p-xylene by catalyzing 5-hydroxymethylfurfural using the Pt@OM-SnO2-T catalyst prepared in Example 3-6, comprising the following steps:

[0061] 1 mmol HMF, 50 mg catalyst and 10 mL THF were added to a high-pressure reactor. After the residual air in the reactor was purged with an argon stream, 1 MPa H2 was re-injected into it and heated to 120°C under magnetic stirring for 4.5 hours. After the reaction was completed, the reactor was cooled to room temperature, the generated H2-CO2 mixture was flushed with an argon stream, and 6 mmol acrylic acid was introduced into the reactor. The reactor was then heated to 120°C under magnetic stirring for 14 hours. After the reaction was completed, the supernatant was analyzed by a gas chromatograph-mass spectrometer (Agilent, 7890B GC / 5977AMS) equipped with a DB-35MS UI capillary column (0.25 mm×30 m) to determine the conversion rate and selectivity.

[0062] Example 9

[0063] This example provides a method for preparing toluene by catalyzing furfural using the Pt@OM-SnO2-T catalyst prepared in Example 3-6, comprising the following steps:

[0064] 1mmol FFA, 50mg catalyst and 10mL THF were added to a high-pressure reactor. After the residual air in the reactor was blown out with an argon stream, 1Mpa H2 was re-injected into it and heated to 120°C under magnetic stirring for 3.5 hours. After the reaction was completed, the reactor was cooled to room temperature, the generated H2-CO2 mixture was flushed with an argon stream, and 6mmol acrylic acid was introduced into the reactor. The reactor was then heated to 120°C under magnetic stirring for 13 hours. After the reaction was completed, the supernatant was analyzed by a gas chromatograph-mass spectrometer (Agilent, 7890B GC / 5977AMS) equipped with a DB-35MS UI capillary column (0.25mm×30m) to determine the conversion rate and selectivity.

[0065] Example 10

[0066] This example provides a method for catalyzing furan to benzene using the Pt@OM-SnO2-T catalyst prepared in Example 3-6, comprising the following steps:

[0067] 1mmol furan, 6mmol acrylic acid, 50mg catalyst and 10mL THF were added to a high pressure reactor. After the residual air in the reactor was purged with an argon stream, the reactor was heated to 120°C under magnetic stirring for 14 hours. After the reaction was completed, the supernatant was analyzed by a gas chromatograph-mass spectrometer (Agilent, 7890B GC / 5977A MS) equipped with a DB-35MS UI capillary column (0.25mm×30m) to determine the conversion rate and selectivity.

[0068] Comparative Example 1

[0069] The method provided in Example 8 was used to catalyze 5-hydroxymethylfurfural to produce p-xylene, except that a solid tin oxide-supported Pt-based nanoparticle catalyst (Pt@S-SnO2-350) reduced at 350°C was used instead of the Pt@OM-SnO2-T catalyst, and the other steps and parameters were the same.

[0070] The preparation method of the Pt@S-SnO2-350 catalyst is similar to that of Example 5, except that the carrier uses solid tin oxide instead of ordered mesoporous tin oxide. The preparation method of solid tin oxide is similar to that of Example 2, except that no ordered silica template is added.

[0071] Comparative Example 2

[0072] The method provided in Example 9 was used to catalyze furfural to produce toluene, except that Pt@S-SnO2-350 catalyst was used instead of Pt@OM-SnO2-T catalyst, and the other steps and parameters were the same.

[0073] Comparative Example 3

[0074] The method provided in Example 10 was used to catalyze furan to produce benzene, except that Pt@S-SnO2-350 catalyst was used instead of Pt@OM-SnO2-T catalyst, and the other steps and parameters were the same.

[0075] Table 1 The yield of biomass-based furan compounds converted to corresponding BTpX by different catalysts

[0076]

[0077] As can be seen from Table 1, among all the catalysts, the Pt@OM-SnO2-350 catalyst exhibited the highest activity in the catalytic conversion of furan, furfural and 5-hydroxymethylfurfural to benzene, toluene and p-xylene, with yields of 94.6%, 94.2% and 95.2%, respectively, and is a new tandem catalytic system that can achieve high yields of BTpX products from the corresponding biomass-based furan. This excellent catalytic result can be attributed to the excellent mass transfer capacity of the Pt@OM-SnO2-350 catalyst and the favorable strong metal-support interaction between the active sites of Pt1Sn1 iNPs and the OM-SnO2 support.

[0078] In order to verify the reusability of the catalyst provided in this application, the performance repeatability test of the Pt@OM-SnO2-350 catalyst prepared in Example 5 was carried out as follows:

[0079] The Pt@OM-SnO2-350 catalyst used in implementation cases 8-10 was simply separated from the reaction liquid by filtration. The obtained sample was washed three times with deionized water and ethanol, and then dried in a vacuum drying oven at 60°C for 12 hours. The obtained catalyst was then used again in the above-mentioned cases 8-10, and this cycle was repeated 10 times.

[0080] Fig. 9 The catalytic stability performance evaluation results of the Pt@OM-SnO2-350 catalytic material prepared in Example 5 of the present invention for catalytic conversion of various biomass-based furan compounds into biomass-based BTpX. Thanks to the protection of the tin dioxide capping layer on the Pt1Sn1 iNPs, the yield of BTpX did not decrease significantly after 10 reaction cycles, indicating that Pt@OM-SnO2-350 has excellent catalytic stability.

[0081] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing benzene, toluene and p-xylene using raw materials containing furan structures, wherein the raw materials containing furan structures are furan, furfural and 5-hydroxymethylfurfural respectively when preparing benzene, toluene and p-xylene, characterized in that: An ordered mesoporous tin oxide anchored platinum-tin intermetallic compound is used as a catalyst, and in the presence of hydrogen and a solvent, furan, furfural and 5-hydroxymethylfurfural are catalytically converted into benzene, toluene and p-xylene respectively through hydrogenolysis and / or Diels-Alder reaction; the raw material containing the furan structure is also called a biomass-based furan compound, and its mass ratio to the catalyst is 1:0.1-1.

2. The method according to claim 1, characterized in that The solvent is one of tetrahydrofuran, N,N-dimethylformamide and methanol.

3. The method according to claim 1, characterized in that The hydrogen pressure is 0.01-4Mpa.

4. The method according to claim 1, characterized in that The reaction time is 5 to 30 hours.

5. The method according to claim 1, characterized in that The reaction temperature is 30-200°C.

6. The method according to claim 1, characterized in that The preparation method of the catalyst ordered mesoporous tin oxide anchored platinum tin intermetallic compound comprises the following steps: 1) Ordered mesoporous tin oxide materials were synthesized using ordered silica as a template; 2) Adsorbing the ordered mesoporous tin oxide material obtained in step 1) with a platinum metal precursor solution by an equal volume impregnation method, and drying; 3) The powder product obtained in step 2) is reduced at high temperature to obtain an ordered mesoporous tin oxide anchored platinum-tin intermetallic compound material.

7. The method according to claim 6, characterized in that Step 2) The platinum metal precursor solution is one of chloroplatinic acid, platinum chloride and platinum nitrate solutions.

8. The method according to claim 6, characterized in that Step 2) The drying is vacuum drying at a temperature of 50 to 80° C. for 6 to 24 hours.

9. The method according to claim 6, characterized in that Step 3) The calcination atmosphere is H2 / Ar, the heating rate is 1-5°C / min, the temperature is 200-500°C, and the time is 1-6 hours.

10. A catalyst prepared by the method according to any one of claims 6 to 9, characterized in that: The catalyst is an ordered mesoporous tin oxide anchored platinum-tin intermetallic compound. The ordered mesoporous tin oxide has a length of 800-1200 nm, a width of 550-750 nm, and a pore size of 20-27 nm. The crystal phase of the platinum-tin intermetallic nanoparticles is adjustable and can be converted from Pt nanoparticles (NPs) to Pt3Sn1 intermetallic nanoparticles (iNPs) and finally to Pt1Sn1iNPs as the temperature increases.